The Impact of Education on Achieving the Sustainable Development Goals - Mahon, Dominic; Arnab, Sylvester; Avezahra, Mutia Husna; Fadhli, Muhibuddin; Mahon, Anastassiya; Masters, Alex; Purnomo, Rochmat Aldy; Wimpenny, Katherine (Sospol, 2025)
This article explores the critical role of education in achieving the Sustainable Development Goals (SDGs), with a particular focus on SDG 4: Quality Education. Through an analysis of the challenges and opportunities inherent in the current educational landscape, this paper highlights the need for innovative, inclusive, and contextually appropriate educational strategies. The discussion extends to the impact of education on other key SDGs, including SDG 13: Climate Action, SDG 16: Peace, Justice, and Strong Institutions, and SDG 8: Decent Work and Economic Growth. Drawing on a conceptual and literature-based analysis of interdisciplinary scholarship in education, development studies, and public policy, the article argues that education’s impact on sustainable development is contingent upon the alignment between pedagogical approaches and the socio-economic, cultural, institutional, and technological contexts in which learning takes place.